Hyla prasina Burmeister, 1856 meets the requirements of Article 23.9.1 of the Code for a reversal of precedence over Hyla quoyi Bory de Saint-Vincent, 1828 (Anura, Hylidae) - Kolenc, Francisco; Baldo, Diego (Zootaxa, 2018)
In a recent work, Ohler and Dubois (2018) discussed the correct application of Article 23.9 of the Code (Anonymous, 1999; 2012) and illustrated it with some concrete cases in which the authors considered that the Article was misinterpreted. Article 23.9 of the Code allows the “reversal of precedence”, that is, that when a senior homonym or synonym has not been used as a valid nomen after 1899 (Article 23.9.1.1) and its junior synonym or homonym has been used as valid for the same taxon in at least 25 works published by at least 10 authors in the immediately preceding 50 years and encompassing a span of not less than 10 years (Article 23.9.1.2), the junior homonym or synonym must be maintained as valid (Article 23.9.1). One of the cases considered by Ohler and Dubois (2018) is the treatment given by Caramaschi and Niemeyer (2010) to the names Hyla prasina Burmeister, 1856 (under the combination Hypsiboas prasinus), and Hyla quoyi Bory de Saint-Vincent, 1828.